Human‐Induced Risk Drives Behavioural Decisions in a Recovering Brown Bear Population - Andrea Corradini; Daniele Falcinelli; Luca Pedrotti; Clara Tattoni; Nathan Ranc; Natalia Bragalanti; Claudio Groff; Marco Ciolli; Francesca Cagnacci (Animal Conservation, 2024)
In human-dominated landscapes, rebounding bear populations share space with people, which may lead to bear–human conflicts and, consequently, a decrease in acceptance and an increase in bear mortality linked to human causes. Previous analyses of brown bear (Ursus arctos) movement data have shown that bears adopt a security-food trade-off strategy in response to variable human-related risk. However, brown bear flexibility to cope with these risky situations may be reduced when resting, mating or stocking fat in preparation for hibernation. In this study, we measured the multi-scale spatial response of brown bears to human-related risk and food resource distribution in a highly heterogeneous human-dominated landscape. We examined habitat selection both within the population range (‘second-order’ selection) and at bedding site locations (‘third-order’) for GPS-tagged brown bears of a recently reintroduced population in the Italian Alps. We identified resting locations by field-validated spatio-temporal cluster analysis of telemetry locations. We mapped food availability and distribution using dynamic geographic layers of fruiting wild berries, and human-related risk using human mobility data (Strava-based Cumulated Outdoor activity Index). Brown bears appeared to compromise their need for food resources for avoidance of anthropogenic disturbance when selecting home ranges, as they utilized areas richer in wild berries less when human use of outdoor tracks was higher. Furthermore, selection of resting site locations strongly depended on the avoidance of human-related risk only, with less frequented, more concealed and inaccessible sites being selected. We conclude that humans compete for space with bears beyond their infrastructural impact, that is, by actively occupying key areas for bear survival, thereby potentially restricting the bears’ realized niche. We propose mitigating actions to promote bear–human coexistence by selectively restricting human access to key areas during sensitive annual physiological phases ...